Approaches,Levels,and Methods of Analysis in International Politics - STARR, Harvey (Palgrave, 2006)
Leading scholars incorporate domestic and international aims, choices, factors, and processes to explore the advantages of crossing methodological and analytical boundaries to gain a better understanding of international relations. They examine the complexity of international affairs and consider how scholars should best study it.